2006
DOI: 10.1007/s11146-005-5177-9
|View full text |Cite
|
Sign up to set email alerts
|

How Does Appraisal Smoothing Bias Real Estate Returns Measurement?

Abstract: This paper examines and clarifies several related issues about real estate return indexes. Specifically, even if real estate valuation smoothing exists at the individual property level, such errors may offset in the aggregate. Using data from commercial property appraisals and corresponding transactions, appraisal smoothing errors engender an underestimation of both the first and second moments for real estate returns. After correcting for these “underestimations,” real estate mean returns and the variance app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…This leads to a moving average of current and past value estimates, which by definition, creates serial correlation and hence the smoothing effect. After the development of the partial adjustment model by Blundell & Ward (1987), Geltner (1989Geltner ( , 1991 and Quan & Quigley (1989, 1991, many authors have found empirical support for appraisal smoothing (Matysiak & Wang, 1995;Diaz & Wolverton, 1998;Fisher & Geltner, 2000;Clayton et al, 2001;Edelstein & Quan, 2006;Cannon & Cole, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a moving average of current and past value estimates, which by definition, creates serial correlation and hence the smoothing effect. After the development of the partial adjustment model by Blundell & Ward (1987), Geltner (1989Geltner ( , 1991 and Quan & Quigley (1989, 1991, many authors have found empirical support for appraisal smoothing (Matysiak & Wang, 1995;Diaz & Wolverton, 1998;Fisher & Geltner, 2000;Clayton et al, 2001;Edelstein & Quan, 2006;Cannon & Cole, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Econ and MicMacG, have overall a relative importance of about 14% for appraisers and 27% for investors. Given this finding, it is not surprising that appraisal-based real estate indices have been found to be smoothed (Matysiak & Wang, 1995;Diaz & Wolverton, 1998;Fisher & Geltner, 2000;Clayton et al, 2001;Edelstein & Quan, 2006;Cannon & Cole, 2011). As appraisers underweight variables that change over time at the cost of variables that hardly change over time, it seems plausible that appraisal-based values are smoother than transaction prices.…”
mentioning
confidence: 99%
“…Third, revised values to private equity and venture capital generally are triggered by the addition of new investor capital to the portfolio company-and remain at cost until the next round of financing. Finally, Edelstein and Quan [2006] and Geltner, MacGregor, and Schwann [2003] showed that real estate values are typically based on appraisal values that, in turn, are based on historical, not current, values.…”
Section: Measuring Liquidity Premiums For Illiquid Assetsmentioning
confidence: 99%
“…the market 22 For example, this is assumed in Barkham and Geltner (1994). Edelstein and Quan (2005) empirically research the relation between smoothing levels in series for individual properties and indices for real estate markets. Edelstein and Quan (2005, p. 5) state: "To the best of our knowledge, no one has statistically modeled and quantified the effects of aggregation errors upon real estate rates of return indexes."…”
Section: The Bond and Hwang-proceduresmentioning
confidence: 99%